ANALYSIS OF JOB SATISFACTION BASED ON LEADERSHIP STYLE AND LEADER’S ATTITUDE AT PT X - MANADO - Wongso, Marchelina (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
People who already have a job in a company called employee. Employee is human resources that already have a job. If a manager make a mistake when hired employee, it will have a bad impact on employee job performance. Bad job performance will impact employee’s work result, and finally, will affect company development. Employee that disappointed and dissatisfied with job will cease from work and the worst is there will be a negative issue on the company and it will scratch company image. The objectives of this research based on the problem that mention above are to examine employee job satisfaction based on leadership style and leader’s attitude at PT X - Manado. Theories supporting research are human resource management, leadership style, leader’s attitude, and job satisfaction. The population of this research is employees of PT X – Manado with sample of 9 respondents of PT X – Manado. Results and conclusions are leadership style and leader’s attitude has influence towards employee job satisfaction. To gain the job satisfaction, leader also must maximize the togetherness toward employees.Keywords: job satisfaction, leadership style, leader’s attitude